The influence of dopants on the nucleation of semiconductor nanocrystals from homogeneous solution - Bryan, J Daniel; Schwartz, Dana A; Gamelin, Daniel R (Journal of nanoscience and nanotechnology, 2005)
The influence of Co2+ ions on the homogeneous nucleation of ZnO is examined. Using electronic absorption spectroscopy as a dopant-specific in-situ spectroscopic probe, Co2+ ions are found to be quantitatively excluded from the ZnO critical nuclei but incorporated nearly statistically in the subsequent growth layers, resulting in crystallites with pure ZnO cores and Zn(1-x)Co(x)O shells. Strong inhibition of ZnO nucleation by Co2+ ions is also observed. These results are explained using the classical nucleation model. Statistical analysis of nucleation inhibition data allows estimation of the critical nucleus size as 25 +/- 4 Zn2+ ions. Bulk calorimetric data allow the activation barrier for ZnO nucleation containing a single Co2+ impurity to be estimated as 5.75 kcal/mol cluster greater than that of pure ZnO, corresponding to a 1.5 x 10(4)-fold reduction in the ZnO nucleation rate constant upon introduction of a single Co2+ impurity. These data and analysis offer a rare view into the role of composition in homogeneous nucleation processes, and specifically address recent experiments targeting formation of semiconductor quantum dots containing single magnetic impurity ions at their precise centers.